P2Y12 inhibitor versus aspirin monotherapy for secondary prevention of cardiovascular events: meta-analysis of randomized trials. Issue 2 (21st March 2022) - Aggarwal, Devika; Bhatia, Kirtipal; Chunawala, Zainali S; Furtado, Remo H M; Mukherjee, Debabrata; Dixon, Simon R; Jain, Vardhmaan; Arora, Sameer; Zelniker, Thomas A; Navarese, Eliano P; Mishkel, Gregory J; Lee, Cheong J; et al.
Abstract: Aim: To compare the efficacy and safety of P2Y12 inhibitor or aspirin monotherapy for secondary prevention in patients with atherosclerotic cardiovascular disease (ASCVD). Methods and results: Medline, Embase, and Cochrane Central databases were searched to identify randomized trials comparing monotherapy with a P2Y12 inhibitor versus aspirin for secondary prevention in patients with ASCVD (cardiovascular, cerebrovascular, or peripheral artery disease). The primary outcome was major adverse cardiac events (MACE). Secondary outcomes were myocardial infarction (MI), stroke, all-cause mortality, and major bleeding. A random-effects model was used to calculate risk ratios (RR) and the corresponding 95% confidence interval (CI) and heterogeneity among studies was assessed using the Higgins I 2 value. A total of 9 eligible trials (5 with clopidogrel and 4 with ticagrelor) with 61 623 patients were included in our analyses. Monotherapy with P2Y12 inhibitors significantly reduced the risk of MACE by 11% (0.89, 95% CI 0.84–0.95, I 2 = 0%) and MI by 19% (0.81, 95% CI 0.71–0.92, I2 = 0%) compared with aspirin monotherapy. There was no significant difference in the risk of stroke (0.85, 95% CI 0.73–1.01), or all-cause mortality (1.01, 95% CI 0.92–1.11). There was also no significant difference in the risk of major bleeding with P2Y12 inhibitor monotherapy compared with aspirin (0.94, 95% CI 0.72–1.22, I 2 = 42.6%). Results were consistent irrespective of the P2Y12 inhibitor used. Conclusion: P2Y12 inhibitor monotherapy for secondary prevention is associated with a significant reduction in atherothrombotic events compared with aspirin alone without an increased risk of major bleeding. Graphical Abstract: Graphical Abstract A meta-analysis of 9 randomized trials (61 623 patients) was conducted to compare P2Y12 inhibitor monotherapy versus aspirin monotherapy for secondary prevention of cardiovascular events in patients with established atherosclerotic cardiovascular disease (coronary, cerebrovascular, or peripheral artery disease). The included studies had follow-up periods between 3 and 36 months. Monotherapy with P2Y12 inhibitors (clopidogrel or ticagrelor) significantly reduced the risk of MACE by 11% (0.89, 95% CI 0.84–0.95, I 2 = 0%) and MI by 19% (0.81, 95% CI 0.71–0.92, I 2 = 0%) compared with aspirin monotherapy. There was no significant difference in the risk of stroke, all-cause mortality, or major bleeding. Subgroup analysis revealed that the reduction in MACE with P2Y12 inhibitors was driven by a reduction in recurrence of the qualifying event. CI = confidence interval, P2Y12i = P2Y12 inhibitor, RR = risk ratio.